2022
DOI: 10.3390/ijms23094539
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Enhanced Salt Stress Tolerance in Tomato Seedlings, Involving Phytohormone Equilibrium and Photosynthesis

Abstract: Nitric oxide (NO), as a ubiquitous gas signaling molecule, modulates various physiological and biochemical processes and stress responses in plants. In our study, the NO donor nitrosoglutathione (GSNO) significantly promoted tomato seedling growth under NaCl stress, whereas NO scavenger 2-(4-carboxyphenyl)-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide potassium (cPTIO) treatment reversed the positive effect of NO, indicating that NO plays an essential role in enhancing salt stress resistance. To explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Second, NO may act as a signaling molecule in a chain of events that leads to changes in gene expression [ 30 ]. Exogenous NO application has been shown to influence plant responses to salt stress [ 5 , 28 , 32 , 38 , 39 ], drought stress [ 38 , 40 ], excess light [ 41 ], low and high temperatures [ 42 ], ozone, UV-B [ 42 ], and heavy-metal stress [ 37 , 38 , 43 ]. The information on the impact of NO on plants can sometimes be contradictory, because the effects depend on the plant species and seedling age, as well as the duration, and severity of the abiotic stress [ 31 , 33 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, NO may act as a signaling molecule in a chain of events that leads to changes in gene expression [ 30 ]. Exogenous NO application has been shown to influence plant responses to salt stress [ 5 , 28 , 32 , 38 , 39 ], drought stress [ 38 , 40 ], excess light [ 41 ], low and high temperatures [ 42 ], ozone, UV-B [ 42 ], and heavy-metal stress [ 37 , 38 , 43 ]. The information on the impact of NO on plants can sometimes be contradictory, because the effects depend on the plant species and seedling age, as well as the duration, and severity of the abiotic stress [ 31 , 33 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide is a small signaling molecule and a crucial regulator of the plant life cycle [11], which acts positively during various stages of the plant life cycle, such as germination, flowering, development, and senescence, as well as in the amelioration of abiotic stress [2,18]. Thus, this neutral and tiny redox molecule has a great capacity to spread through the cell membrane and is frequently referred to as a dynamic molecule [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, DEGs related plant hormone ETH, ABA and JA were identified in the MAPK signal pathway during salt stress ( Figure 4 ). ETH is a gaseous hormone involved in various aspects of plant biology, including germination, plant growth, organ senescence and fruit ripening [ 23 , 24 ]. In our study, 11 DEGs related to ETH signaling in the MAPK pathway, including ETH receptor , ETR , EIN/ EIL , ethylene response factor ERF and CHI were regulated under salt stress.…”
Section: Discussionmentioning
confidence: 99%